2015
DOI: 10.1139/apnm-2014-0530
|View full text |Cite
|
Sign up to set email alerts
|

Protein: A nutrient in focus

Abstract: Abstract:Protein is an essential component of a healthy diet and is a focus of research programs seeking to optimize health at all stages of life. The focus on protein as a nutrient often centers on its thermogenic and satiating effect, and when included as part of a healthy diet, its potential to preserve lean body mass. A growing body of literature, including stable isotope based studies and longer term dietary interventions, suggests that current dietary protein recommendations may not be sufficient to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 64 publications
0
43
0
1
Order By: Relevance
“…Feeding studies have demonstrated increased hepatic lipogenesis during high‐carbohydrate (Hi CHO) intake and while the 10%‐12% of energy from protein meets the current recommended minimum protein intake for adults (0.66 g/kg/day of body weight), it is lower than recommended protein intake in children during growth (0.71‐0.75 g/kg/day of body weight) . In addition, the optimal recommended protein intake is currently debated in the nutrition literature and many studies suggest benefits from protein intakes higher than the minimum dietary recommended intake . We previously reported increased resting energy expenditure among participants with LC‐FAODs fed a Hi PRO diet for 6 days .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Feeding studies have demonstrated increased hepatic lipogenesis during high‐carbohydrate (Hi CHO) intake and while the 10%‐12% of energy from protein meets the current recommended minimum protein intake for adults (0.66 g/kg/day of body weight), it is lower than recommended protein intake in children during growth (0.71‐0.75 g/kg/day of body weight) . In addition, the optimal recommended protein intake is currently debated in the nutrition literature and many studies suggest benefits from protein intakes higher than the minimum dietary recommended intake . We previously reported increased resting energy expenditure among participants with LC‐FAODs fed a Hi PRO diet for 6 days .…”
Section: Introductionmentioning
confidence: 92%
“…We previously reported increased resting energy expenditure among participants with LC‐FAODs fed a Hi PRO diet for 6 days . Greater dietary protein intake with a reduced carbohydrate intake in the general population is associated with a reduced risk of age‐related sarcopenia while maintaining a healthy body weight …”
Section: Introductionmentioning
confidence: 99%
“…The recommended daily minimum intake of protein and amino acids (AAs) in adults is 0.8 g/kg of body weight (4). However, recent studies using stable isotope suggest that current dietary protein recommendation may not be sufficient to promote optimal muscle physiology in all populations (5). Epidemiological studies support the notion that especially in the older population, a greater protein intake, up to 19% of the energy, better preserves lean body mass (LBM) (6).…”
Section: Protein Quantity/qualitymentioning
confidence: 99%
“…Indeed, the suboptimal skewed protein distribution evident in the general population (Arentson‐Lantz et al . ) remains to be confirmed in athletes and active adults.…”
Section: Current Concepts Informing Protein Requirements For Athletesmentioning
confidence: 97%
“…The ingestion pattern of 4 × 20 g every 3 hours reflects an ‘even’ distribution of protein intake, as opposed to the ‘skewed’ distribution that is typical of the general population (Arentson‐Lantz et al . ), whereby small to modest amounts of protein are eaten at breakfast and lunch, and large intakes are seen at later meal(s) of the day (Fig. ).…”
Section: Current Concepts Informing Protein Requirements For Athletesmentioning
confidence: 99%